MORFOLOGI VEGETATIF JENIS POHON TENGKAWANG (Shorea spp) DI DESA MENSIAU KECAMATAN BATANG LUPAR KABUPATEN KAPUAS HULU - . Riska; Togar Fernando Manurung (Universitas Tanjungpura, 2018)
Tengkawang is a Shorea tree which includes in Dipterocarpacea family. This tree was the indigenous species of West Kalimantan, and mostly found in Kapuas Hulu Regency. Tengkawang seed which is the mascot of West Kalimantan Province was used to produce vegetable oil, chocolate, medicine, margarine, candles, and cosmetics. One of the villages which famous on Tengkawang products were Mensiau village which located in Batang Lupar sub district, Kapuas Hulu Regency. The objective of research was to inventory the diversity of Tengkawang tree in Mensiau village, Batang Lupar sub district, Kapuas Hulu Regency, and identification and made a description on morphology of Tengkawang tree. The research was conducted from May until August 2017. The methods used exploration on four lines in the forest of Mensiau village. The research found total individuals of Tengkawang tree was 1,689 trees. There were five types of Tengkawang, namely Shorea stenoptera, Shorea beccariana, Shorea pinanga, Shorea seminis and Shorea macrophylla. The local names of Tengkawang in Mensiau village were Engkabang Tungkul, Engkabang Rambai, Engkabang Trindak, and Engkabang Biasa. The total individuals of Shorea stenoptera was 408 tree, Shorea beccariana was 571 tree, Shorea pinanga was 370 tree, Shorea seminis was 186 tree and Shorea macrophylla was 154 tree. The efforts on conservation of Tengkawang tree in Mensiau village was needed because the forest in the village was suitable for the habitat of Tengkawang. Keywords : Kapuas Hulu, Shorea beccariana, Shorea macrophylla, Shorea pinanga, Shorea seminis, Shorea stenoptera, Tengkawang